Field report, Spring 1994, Thomas Kent - Kent, Thomas H. (Thomas Hugh), 1934-et al (1994)
An annotated list of birds sighted by Thomas Kent dated May 10, 1994. This item was used as supporting documentation for the Iowa Ornithologists' Union Quarterly field report of Spring 1994. Plustek - flatbed